Economic crime and mechanisms to combat it in Algerian legislation - Cheddadi, Mohcen (The International tax journal, 2025)
Economic crime represents one of the most significant challenges confronting national economies, exerting a direct and adverse impact on their stability and security. These crimes are characterized by their complexity, adaptability, and the evolving methods by which they are perpetrated, particularly in the context of scientific advancement and technological development. Consequently, many countries—especially those in the Global South—struggle considerably to combat such crimes due to the intricate interplay of legal, economic, and social dimensions. Nonetheless, this should by no means preclude the possibility of successfully addressing or at least mitigating these crimes through the adoption of a well-formulated policy and strategy. Such a strategy should focus on the development of relevant legal frameworks and the reinforcement of financial oversight mechanisms, both at the national and international levels.